Magnetic transition and large magnetocaloric effect associated with surface spin disorder in Co and CocoreAgshell nanoparticles - Poddar, P.; Srinath, S.; Gass, James; Bhagavatula L. V. Prasad; Srikanth, H. (Journal of Physical Chemistry C, 2007)
We report a reversible, large magnetocaloric effect in the vicinity of a low-temperature magnetic transition in Co and CocoreAgshell nanoparticles synthesized using a wet chemical method. The as-synthesized assembly of the particles shows a sharp low-temperature peak in the zero-field-cooled (ZFC) magnetization well below the blocking transition temperature, and this feature is associated with the surface spin disorder. Co nanoparticles show a large increase in the magnetic entropy at around 15 K with a peak value of nearly 2.25 J/K center dot kg for an applied field of 30 kOe. A similar trend is also observed in the silver-coated Co particles. These are some of the largest NICE values observed in nanoparticles to date. The features are ascribed to the low-temperature spin-glass-like freezing transition associated with the surface spins in the shell region that is distinct from the behavior of core spins. Our studies reveal that manipulating the surface anisotropy in core-shell nanoparticles has the potential to lead to a large NICE effect and thus prove to be useful for magnetic refrigeration.

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Melting characteristics of superlattices of alkanethiol-capped gold nanoparticles: the ``excluded'' story of excess thiol - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemistry of Materials, 2010)
Melting characteristics of gold nanoparticle superlattices obtained from nanoparticles capped by alkanethiols of different chain lengths (octane, dodecane and hexadecane) have been investigated. The alkanethrol capped nanoparticles were synthesized by the well-established digestive ripening method It is observed that as the chain length Of the thiol increases, the propensity to form superlattices decreases and the melting of the superlattice is observed at lower temperature However, the Formation of the 3D superlattice is critically dependent on the presence of ``excess'' thiol as determined from thermogravimetric and transmission electron microscope analysis. In the absence of ``excess'' thiol, only 2D hexagonally close-packed arrangements were seen

Many manifestations of digestive ripening: monodispersity, superlattices and nanomachining - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2011)
Digestive ripening has now been established as a very convenient route to obtain monodisperse nanoparticles from polydisperse ones by refluxing the latter in the presence of an excess ligand. Many ligands including long chain thiols, amines, or phosphines have been shown to be effective digestive ripening agents. It is hypothesized that the surface active groups of such digestive ripening agents bind and remove reactive surface atoms/clusters from big nanoparticles and redeposit them on smaller nanoparticles. In this way, large particles become smaller, while small particles become larger, and eventually, an equilibrium size is obtained that is specific to each of the digestive ripening agents used. Herein, the digestive ripening procedure is reviewed, discussed and its utility spanning the preparation of monodispersed metal nanoparticles, alloy nanoparticles, superlattice structures and the most interesting nano-machining (wherein the monodisperse particles can be reverted back to the polydisperse system) is demonstrated.

Microfluidic platform for continuous flow synthesis of triangular gold nanoplates - Kumar, D. V. Ravi; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
A microfluidic platform for the continuous flow synthesis of triangular gold nanoplates with and without surfactants is developed. The temperature profile in the microchannel, residence time and composition have been studied to understand effect of these parameters on the yield of the triangular nanoplates and were optimized for obtaining maximum yield of triangles. The flow synthesis approach has been demonstrated where the Br- ions can be supplied to the reaction mixture either from the surfactant viz. Cetyl trimethylammonium bromide (CTAB) or even from HBr. Apart from the Br- ions, the temperature gradient at the inlet of the continuous flow reactor is one of the key parameter that affects the yield of the triangular nanoplates. Finally we establish that with a right combination of the controlling parameters abetter yield of the Au nanotriangles by flow methods can be achieved even in the absence of surfactant. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Flow synthesis; microreactor; Nucleation kinetics; Surfactants